Trade in Financial Services and Capital Movements - Tamirisa, Natalia (Washington, D.C. : International Monetary Fund, 1999)
International financial liberalization may alter saving-investment imbalances and patterns of capital flows across countries. In a panel of OECD countries for 1990-96, this study examines how the liberalization of capital movements and financial services trade affects net private capital flows. Capital inflows tend to fall (rise) with the liberalization of commercial presence in banking and securities (insurance) services, possibly reflecting an increase (decrease) in saving. Capital account liberalization is found to stimulate capital inflows, suggesting that better access to external financing helps sustain larger fiscal and current account deficits. When cross-border trade is liberalized, capital flows change insignificantly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet